Association between parenthood and survival among 30,386 patients hospitalized with COVID-19 - Etienne Audureau; Charline Jean; Richard Layese; Antoine Neuraz; Paul Brasseur; Nadia Oubaya; Laura Polivka; Arsène Mekinian; Olivier Hermine; Julien Rossignol (PLoS ONE, 2026)
Background Cross-reactive immune responses between endemic human coronaviruses and SARS-CoV-2 have been proposed as a potential factor mitigating COVID-19 severity. Because parents may have more frequent exposure to seasonal respiratory viruses through contact with children, we investigated whether parental status was associated with improved survival among adults hospitalized with COVID-19. Methods We conducted a retrospective cohort study using the Assistance Publique–Hôpitaux de Paris (AP-HP) Clinical Data Warehouse. We included all adults (≥18 years) hospitalized with RT-PCR–confirmed SARS-CoV-2 infection between January 29, 2020 and March 1, 2022. The primary endpoint was 90-day mortality after admission, analyzed as a time-to-event outcome using Cox proportional hazards models adjusted for demographics, comorbidities, admission period (pandemic wave), and baseline biological variables. Parental status was extracted from electronic health record text reports. We tested for interaction between age and parental status. Results Among 30,386 patients, 22,713 (75%) were classified as having children. Compared with patients without children, those with children were older and had more comorbidities. In the overall adjusted analysis, parental status was not associated with 90-day survival (HR = 1.00, 95%CI 0.94–1.07; p = 0.91). The association between parental status and survival was significantly modified by age (p interaction = 0.002), with an association with lower mortality observed in younger adults that attenuated toward the null in older age groups. After stratification by age (<65 vs ≥ 65 years), having children was associated with improved 90-day survival in patients <65 years (Hazard Ratio (HR)=0.83, 95%CI 0.72–0.95; p = 0.009), whereas no significant association was observed in patients ≥65 years (HR = 1.07, 95%CI 0.99–1.15; p = 0.09). Conclusions In this large EHR-based cohort of adults hospitalized with COVID-19, parenthood was associated with lower 90-day mortality among patients younger than 65 years. These findings are observational and may reflect unmeasured confounding; further studies are needed to clarify underlying mechanisms.